2014
DOI: 10.1371/journal.pone.0104044
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA Expression Profiles of Lung Adenocarcinoma Ascertained by Microarray Analysis

Abstract: BackgroundLong noncoding RNAs (lncRNAs) have been shown to be involved in the development and progression of lung cancer. However, the roles of lncRNAs in lung cancer are not well understood.Methodology/Principal FindingsWe used a high-throughput microarray to compare the lncRNA and messenger RNA (mRNA) expression profiles in lung adenocarcinoma and normal tissue (NT) samples. Several candidate adenocarcinoma-associated lncRNAs were verified by real-time quantitative reverse transcription polymerase chain reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 26 publications
1
62
0
Order By: Relevance
“…Recently, Xu and his colleagues has reported that LINC00858 is highly expressed in lung adenocarcinoma (5.23-fold than normal lung tissues) [12], while until now, the relevance between LINC00858 expression and NSCLC tumorigenesis has not been elaborated yet. Hence, the roles and potential biological mechanisms of LINC00858 on NSCLC still remain to be expounded.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Xu and his colleagues has reported that LINC00858 is highly expressed in lung adenocarcinoma (5.23-fold than normal lung tissues) [12], while until now, the relevance between LINC00858 expression and NSCLC tumorigenesis has not been elaborated yet. Hence, the roles and potential biological mechanisms of LINC00858 on NSCLC still remain to be expounded.…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer has become the most common cancer, and the incidence rate of lung cancer is gradually growing [14]. About 80%–85% of the newly diagnosed lung cancers are non-small cell lung cancer (NSCLC) [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, using high-throughput microarrays, Xu et al identified 2420 lncRNAs that were differentially expressed (fold change ⩾2) between LAD and normal tissue (NT) samples. Of these 2420 lncRNAs, the expression of 1213 lncRNAs was upregulated, whereas the expression of the remaining 1207 lncRNAs was downregulated [48]. As another example, Yang et al identified 47 lncRNAs (14 upregulated and 33 downregulated lncRNAs) from gene expression data of five NSCLC cohorts that were deposited in the Gene Expression Omnibus (GEO) database [49].…”
Section: Expression Spectrum Of Lncrnas In Nsclcsmentioning
confidence: 99%